APP deficiency results in resistance to obesity but impairs glucose tolerance upon high fat feeding. Issue 3 (June 2018) - Czeczor, Juliane K; Genders, Amanda J; Aston-Mourney, Kathryn; Connor, Timothy; Hall, Liam G; Hasebe, Kyoko; Ellis, Megan; De Jong, Kirstie A; Henstridge, Darren C; Meikle, Peter J; Febbraio, Mark A; Walder, Ken; et al.
Abstract : The amyloid precursor protein (APP) generates a number of peptides when processed through different cleavage mechanisms, including the amyloid beta peptide that is implicated in the development of Alzheimer's disease. It is well established that APP via its cleaved peptides regulates aspects of neuronal metabolism. Emerging evidence suggests that amyloidogenic processing of APP can lead to altered systemic metabolism, similar to that observed in metabolic disease states. In the present study, we investigated the effect of APP deficiency on obesity-induced alterations in systemic metabolism. Compared with WT littermates, APP-deficient mice were resistant to diet-induced obesity, which was linked to higher energy expenditure and lipid oxidation throughout the dark phase and was associated with increased spontaneous physical activity. Consistent with this lean phenotype, APP-deficient mice fed a high-fat diet (HFD) had normal insulin tolerance. However, despite normal insulin action, these mice were glucose intolerant, similar to WT mice fed a HFD. This was associated with reduced plasma insulin in the early phase of the glucose tolerance test. Analysis of the pancreas showed that APP was required to maintain normal islet and β-cell mass under high fat feeding conditions. These studies show that, in addition to regulating aspects of neuronal metabolism, APP is an important regulator of whole body energy expenditure and glucose homeostasis under high fat feeding conditions.